Candidate genetic determinants of intraspecific variation in pea aphid susceptibility to RNA interference. (August 2020) - Yoon, June-Sun; Tian, Hong-gang; McMullen, John G.; Chung, Seung Ho; Douglas, Angela E.
Abstract: RNA interference (RNAi) plays a key role in insect defense against viruses and transposable elements, and it is being applied as an experimental tool and for insect pest control. However, RNAi efficiency is highly variable for some insects, notably the pea aphid Acyrthosiphon pisum . In this study, we used natural variation in RNAi susceptibility of pea aphids to identify genes that influence RNAi efficiency. Susceptibility to orally-delivered dsRNA against the gut aquaporin gene AQP1 (ds- AQP1 ) varied widely across a panel of 83 pea aphid genotypes, from zero to total mortality. Genome-wide association between aphid performance on ds- AQP1 supplemented diet and aphid genetic variants yielded 103 significantly associated single nucleotide polymorphisms (SNPs), including variants in 55 genes, at the 10 −4 probability cut-off. When ds- AQP1 was co-administered with dsRNA against six candidate genes, aphid mortality was reduced for three (50%) genes: the orthologs of the Drosophila genes trachealess (CG42865), headcase (CG15532) and a gene coding a peritrophin-A domain (CG8192), indicating that these genes function to promote RNAi efficiency against AQP1 in the pea aphid. Aphid susceptibility (quantified as mortality) to ds- AQP1 was correlated with RNAi against a further gene, snakeskin with essential gut function unrelated to AQP1, for some but not all aphid genotypes tested, suggesting that the determinants of RNAi efficiency may be partly gene-specific. This study demonstrates high levels of natural variation in susceptibility to RNAi and demonstrates the value of harnessing this variation to identify genes influencing RNAi efficiency. Graphical abstract: Image 1 Highlights: RNAi susceptibility varies widely among pea aphid genotypes. Pea aphid RNAi susceptibility is correlated with SNPs in multiple aphid genes. Correlated genes are enriched in functions related to RNA/DNA processes. RNAi-of-RNAi experiments identify three genes that promote RNAi.